PROTOTYPE PINTU PAGAR OTOMATIS BERBASIS ARDUINO UNO R3 - Rahman, Rahman; Wirawan, Raden; Halik, Sri Asfirawati (CV. LAJAGOE PUSTAKA, 2024)
This study aims (1) to make a prototype of an automatic gate based on arduino uno R3. (2) To see the user's response to the Arduino Uno R3-based automatic gate prototype. The research method used in this study is the Prototype Method. In this case the prototyping method is very suitable for use in terms of developing and designing a prototyping system which starts with Requirements Gathering, Prototype Building, System Coding, System Testing, System Evaluation, Using the System. In this case it can be concluded that: 1). The Arduino uno R3-based automatic gate prototype can open and close automatically using the Arduino uno R3 component. The ultrasonic sensor is used to detect the presence of objects, and the servo motor drives the gate so that the door can open automatically. 2). The Arduino uno R3-based automatic gate prototype in the process after the sensor detects the presence of an object, the received data is forwarded to the arduino uno R3 to be processed, after that the data is forwarded to the servo motor so that the door can open automatically. and From the analysis of the data obtained from the user's response to the Arduino uno R3-based automatic gate prototype, it received positive responses, this can be seen in the total average presentation of 88.2% (A), which means the category is very good.